Upaya Guru dalam Membentuk Karakter Kreativitas Siswa dalam Pembelajaran IPA di Sekolah Dasar - Riyadi, Ahmad Rifky; Azmi, Fikri Haikal; Musa, Muhamad; Anisah, Aan; Alpian, Yayan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Teaching science is very important to be given to all students starting from elementary school. This is aimed at equipping students with logical, analytical, systematic, critical, creative thinking skills, and the ability to work together. The skills obtained from learning science are expected to help in facing the progress of technology, information, and communication in the current era of globalization. The type of research that will be used by the author is a theoretical study of a concept to see something comprehensively, to see the relationships that exist in variables, and then used to explain and predict existing phenomena. It can be concluded that using multimedia in the implementation of learning will be more creative and innovative, allowing students to visualize difficult material with the help of conventional tools, and can train learners or students to be more independent and active in the learning process. Thus, teachers can foster the creativity of students in science learning so that the implementation of online learning processes still makes students active in learning.